-x+6x=-9

Simple and best practice solution for -x+6x=-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x+6x=-9 equation:



-x+6x=-9
We move all terms to the left:
-x+6x-(-9)=0
We add all the numbers together, and all the variables
5x+9=0
We move all terms containing x to the left, all other terms to the right
5x=-9
x=-9/5
x=-1+4/5

You can always share this solution

See similar equations:

| 5x+12=3+6x | | -1.7s-19.98=13.9s+20+11.5 | | 5x-45+4x=3-10x+9 | | 36?9u=??27 | | 5d+9=9 | | Y=-(x-1)^2+25 | | x^2+18=8 | | -w+9=-7+8w-8w | | -1.32=3(1.5y-0.5) | | 8b=23-111 | | -17+4c=11c+5-5c | | 8b=56b= | | -5-6h=7 | | 13+20f=4f-17+18f | | 15x+5=80+6x6 | | 13+15q+8=20q-19 | | 5m-15=2m-9 | | 16/(x-3)=10/x | | -16-8t+5t=t+20 | | r-7/6=5 | | 18+12k=13k | | 8u=54+2u | | -4x+3.4=5x=1.1 | | v-5.7=9.79 | | 18000+0,18x=x | | 4x-1.8=4x+0.4 | | u+3.1=9.53 | | x-8.5=2.9 | | 3x-12+x+2x+3x+3x=540 | | -5x-2.8=-9+0.4 | | -88=-10+6k | | 5(3x-6)=-105 |

Equations solver categories